Comparison of the Burial Rite of the Lomovatovo and Nevolino Cultures: materials of preliminary research - Artem Al. Nazarov (Археология евразийских степей)
The article presents a comparative analysis of the burial rite of the medieval population of the Kama region: bearers of the Lomovatovo and Nevolino cultures. The individual components of the funeral rite were studied: metric - length, width, depth of burials and qualitative - the shape of grave pits, the number of individuals in the burial, inter-burial structures, tombstone structures and the orientation of the skeleton. The Pearson correlation analysis method was used to establish a link between the various metric components of the burial rite. The burial traditions of the geographically and chronologically closest Azelino and Vym cultures were analyzed, as there is a large number of published reports based on the materials of their burial grounds. It is concluded that the rituals of the Lomovatovo and Nevolino cultures changed due to internal transformations and the influence of bearers of geographically close cultural traditions. Common features have been identified – the presence of tombstone structures, facing frames and usage of birch bark. The conclusion is made about the similar processes of integration of traditions of the newcomer population of the Migration period into the local rite and assimilation of this population with a change of burial rites. However, the Nevolino culture demonstrates a greater number of southern traditions in the rite, while occupying a middle position between the connection of the burial rite metric components in the Lomovatovo and Azelino cultures. The Vym culture does not demonstrate an unambiguous link with Lomovatovo culture. It is possible to assume the perception of different traditions by the bearers of these cultures. Perhaps the burial rites of the Lomovatovo culture were associated with the eastern and northern neighbours, and those of the Nevolino culture - rather with southern ones.